Constitutional values in the conditions of historical continuity - Andrichenko, Lyudmila V.; Maslovskaya, Tatiana S.; Plyugina, Inna V. (Journal of the Belarusian State University. Law, 2024)
The authors of the article examine the issue of historical continuity of constitutional values. The constitution is considered as one of the mechanisms for preserving and transmitting the most important historical experience, which allows for constitutional stability and sustainable development. The significance of the constitution is considered not only in the context of preserving the basic foundations of the state and society, but also in creating conditions for their further development, adaptation to modern realities. It is noted that one of the consequences of the increasingly widespread use of the value approach in legislation is the stratification of the value basis, the allocation of various types of values (constitutional, traditional spiritual and moral, national, etc.), which are not always clearly distinguished.